Faith, freedom, and US foreign policy: Avoiding the proverbial clash of civilizations in East and Southeast Asia - TAN, Eugene K. B. (Institutional Knowledge at Singapore Management University, 2013)
In the immediate aftermath of 9/11, the primary weakness of US foreign policy, particularly in Southeast Asia which is home to the largest Muslim community in the world, was that it was driven by concerns over archipelagic Southeast Asia as the “second front” in the “global war against terror.” Military warfare and coercive legislation and enforcement are grossly inadequate in winning the hearts and minds of a community. Religion-wise, Asia is not a tabula rosa. Many religions have long co-existed in Asia. The virtues of religious freedom are not alien to Asia but need nurturing given the dominant imperatives of governance, control, and economic growth.